LANGUAGE TRANSFER IN LEARNER LANGUAGE - Warsono Warsono (Universitas Islam Sultan Agung, 2016)
In using the foreign language they are learning, learners tend to use forms that deviate from the target language (TL) norms. The question that arises is whether these forms are the result of transfer or the result of some other causes; and if transfer does exist in learner language, whether it diminishes with the development of the learner TL achievement. This paper tries to find answers to these questions by (1) reviewing some related literature, and (2) looking at some data of learners’ written production of Indonesian learners of English. The data were collected from the writings of the fifth semester students of the English Department (group A, representing low level of L2 achievement), and the final projects written by the English Department students (group B, representing high level of L2 achievement). In this paper, all forms that deviate from the TL norms were called errors, irrespective of whether they were, in fact, mistakes or real errors. The learners’ errors were broadly classified into two classes: intralingual errors and interlingual errors, and it was the latter that became the focus of this study on the assumption that interlingual errorswere caused by L1 transfer. The results of data analysis showed that intralingual errors were slightly higher in group A than interlingual ones; but in group B interlingual errors formed the majority of errors made by the learners (75%). It can be concluded that L1 transfer does exist in the L2 of the Indonesian learners of English. The results also showed that L1 transfer does not diminish with the development of the L2 achievement. It is strongly suggested, therefore, that Indonesian English teachers anticipate the errors caused by L1 transfer and find ways to solve the problems.